2016
DOI: 10.11646/zootaxa.4169.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Squalius namak, a new chub from Lake Namak basin in Iran (Teleostei: Cyprinidae)

Abstract: Squalius namak, new species, from the endorheic Lake Namak and Kavir basins in Iran, is distinguished from the species of the genus Squalius in the Persian Gulf and the southern Caspian Sea basins by having a wide and thick symphysial knob on the lower jaw, a convex posterior anal-fin margin, a bold, dark-grey or brown, roundish or crescent-shaped blotch at the posterior tip of each flank scale and orange caudal-, anal- and pelvic-fin rays in life. Squalius namak is also characterized by four fixed, diagnostic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 831 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…2019), and Squalius orintale from the Caspian Sea basin and S. turcicus from the Çoruh River basin share identical COI genes (Khaefi et al . 2016). Therefore, two allopatric species, that is, the C. ekmekciae and C. capoeta forms, have perhaps recently been isolated.…”
Section: Discussionmentioning
confidence: 99%
“…2019), and Squalius orintale from the Caspian Sea basin and S. turcicus from the Çoruh River basin share identical COI genes (Khaefi et al . 2016). Therefore, two allopatric species, that is, the C. ekmekciae and C. capoeta forms, have perhaps recently been isolated.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the parameters of the length–weight and length‐length relationships are reported for three species of Squalius from different basins of Iran. A newly described species is including in the study ( Squalius namak ), which was previously considered to belong to the Squalius cephalus group (Khaefi, Esmaeili, Sayyadzadeh, Geiger, & Freyhof, ).…”
Section: Introductionmentioning
confidence: 99%